Environmental Study of Some Water Characteristics at Um-Al-Naaj Marsh, South of Iraq. - Baghdad Science Journal (مجلة بغداد للعلوم, 2011)
Um-Al-Naaj region in Al-Hawiezah Marsh, Southern Iraq was chosen to study the environmental variations of some water characteristics during 2008, seasonally. The results showed clear seasonal changes in values of some environmental variables (temperature, depth, light penetration, turbidity, total suspended solids, pH, dissolved oxygen, reactive phosphate, reactive nitrite, and reactive nitrate), while there were no clear seasonal changes in electrical conductivity and salinity values. In addition, high nutrients concentrations and light penetration were noted. Statistical analysis showed significant positive relationship between air and water temperature; electrical conductivity and salinity. Water turbidity was significantly affected by total suspended solids. On the other hand, some of the studied variables had significant negative effects (relative relationships) to each other, when water pH and dissolved oxygen were affected by temperature; total suspended solids and turbidity affected also light penetration.